MENTAL HEALTH AND ITS RELATIONSHIP WITH ACADEMIC ADJUSTMENT AMONG FIRST-YEAR STUDENTS IN SOCIAL SCIENCES: A FIELD STUDY CONDUCTED AT THE FACULTY OF SOCIAL AND HUMAN SCIENCES, UNIVERSITY OF HAMMA LAKHDAR – EL OUED - Mohammedi Abderrahmane; Mohammedi Karima; Zidane Djamila (International Journal of Innovative Technologies in Social Science, 2025)
The psychological well-being of first-year university students is a critical factor that has garnered considerable attention from researchers and specialists, as mental health significantly influences academic adjustment, either positively or negatively. Building on this premise, the present study investigates the relationship between mental health and academic adjustment among a sample of 75 first-year students enrolled in the Faculty of Social Sciences at Hamma Lakhdar University of El Oued. The study also examines potential differences in mental health and academic adjustment according to gender. To achieve these objectives, a descriptive research design was employed, utilizing validated and reliable instruments for measuring mental health and academic adjustment. The findings indicate a positive correlation between mental health and academic adjustment (r = 0.679). Furthermore, while no significant gender differences were found in mental health, the results revealed statistically significant differences in academic adjustment, favoring female students.